Beginning Selenium WebDriver testing in Java - Craze, Andy (Packt Publishing, 2018)
"This course will introduce the Java users to Selenium WebDriver. It will help users with basic programming knowledge to start with code testing. This course will help the users to cut down on their time spent on testing code written in Java. Get started with code testing using Selenium WebDriver. It will be an ideal starter kit for those of you who wish to start using Selenium WebDriver for testing. Users with basic programming knowledge more interested in skilling up with Selenium WebDriver as their testing tool of choice. In this course, you will start by knowing the benefits of Selenium WebDriver for testing. You will then start with practicing the basics. Post that you will see the biggest strength of Selenium which is integrating your test instances with the browser of your choice. You will then actually test an authentication system in a sequential manner by following each of the required steps. By the end of the course, you will be able to provide your customers and clients with better quality code in lesser time - adding to your customer delight!"--Resource description page